ChemInform Abstract: A Phosphetane Catalyzes Deoxygenative Condensation of α‐Keto Esters and Carboxylic Acids via PIII/PV=O Redox Cycling. Issue 27 (18th June 2015) - Zhao, Wei; Yan, Patrick K.; Radosevich, Alexander T.
Abstract Reduction of the P‐oxide APO with PhSiH3 affords a tricoordinate aminophosphetane which promotes the title reaction to produce α‐acyloxy esters with a high functional group compatibility.